Kasturi primal - Patil, Vishwas (New Delhi Publication Division, Ministry of Information and Broadcasting, GOI, 2019)
This magazine dedicated to literature, culture and art, published from our department, is now entering its sixtieth year. Such a long journey for a magazines like Dharmayuga, Weekly Hindustan and Sarika have become obsolete, then maintaining its existence nowadays is a sign of its vitality. There is also a lot of love from the readers behind this, Without their love and cooperation, it would not have been possible to complete the sixth decade today.
Keywords: Biography-Women-Kasturba Gandhi